(untitled) (Docentes 2.0 Journal, 2023)
An educational perspective is a useful tool for identifying the challenges and opportunities in educational change and designing strategies with effective policies to improve education. The present essay was framed under the inductive method of a descriptive type, hermeneutic paradigm, with a qualitative approach based on the case studies carried out previously with a narrative design in a subjective way of a topical type accompanied by different perceptions of various authors, which frames the possible future scenarios of the educational system in the country, to establish strategies with policies that allow facing the challenges and taking advantage of the opportunities. In this sense, the educational perspective of Mexico considers factors such as demographic evolution, technological advances, world trends in education, and changes in the economy and society; plans or programs can be designed that respond to the population’s needs that contribute to the country’s development. In addition, it faces various challenges in carrying out effective planning that allows for improving the country’s education quality. However, it is possible to face these challenges by collaborating with different actors and implementing innovative strategies with positive effects. In this way, the challenges and opportunities presented by the future of education in Mexico can be identified, addressed, and understood effectively.